Managing Differences and Maintaining Harmony of Da'wah Organization - Sukardi, Akhmad; Basri, Hasan; Kadir, Ayyub; Pattaling, Pattaling (Al-MUNZIR, 2025)
The problem studied in this paper is the diversity of understanding of Muslims who are institutionalized into organizations and carry out da'wah activities with their own characteristics. The method used is a literature review with an analysis technique that imitates the flexible content analysis method, namely by providing a description of the author's meaning based on expert concepts and understanding and experience of the al-Qur'an and Hadith arguments and other references, both from books and articles and observations of objective reality in the community. The results of the study show that the diversity of da'wah organizations often has the potential to give rise to tension, attitudes of mutual weakening, and disharmony caused by shallow understanding, loss of clarity of understanding, cult of figures, and organizational ego. In order for harmony and cooperation in da'wah organizations to occur, it is necessary to understand that differences are a blessing, while division is a curse, to understand well the matter of qath'iy and zhanniy or the matter of ushul and furu', to direct attention to the ideas conveyed, not figures or organizations, and to focus on the goals of da'wah which are common goals.